DETEMINATION OF CHEMICAL AND BIOCHEMICAL COMPOSITION OF ARTEMIA URMIANA CYST SHELLS AND ITS EXTRACTION CHITIN - Y. Asadpor1; A. Shoja alsadati2; A. Ghoroghi2; M. Kalbasi3; A. Khosroshahi1 (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2003)
Artemia urmiana cyst shells collected, purified and dried from ashore of Rashkhan and Bozorgrah in the Urmia Lakein January and February 2002. According to the results obtained by standard methods of analyses the cyst shell contains: 4.8±0.5% lipid, 32±2% protein, 10.5±1.0% moisture, 0.5±0.2% haematin and 20.6±2.0% total ash. The chemical composition of ash are: Na2O 1.98%, MgO 1.14%, S03 6.82%, CI 3.23%, K20 2.12%, CaO 4.05%, Fe2O3 1.68%, Zn 0.05%. The chitin was extracted from Artemia cyst shells by using different methods of demineralizaion, delipidization, deproteinization and decolorization. The yield of extraction from cyst shells was 28±3%. Composition of chitin was determined by FTIR, X-Ray Powder diffraction and C.H.N.O analyser. Artemia urmiana cyst shell contains approximately about 28±3% percentage chitin.